2017
DOI: 10.17085/apm.2017.12.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of midline depth from skin to cervical epidural space by lateral cervical spine X-ray

Abstract: Background:Previous studies have shown that measuring the distance from the skin to the ligamentum flavum by ultrasound preceding cervical epidural block can be beneficial in excluding false loss of resistance. However, the measurement value using ultrasound may vary depending on the degree of operator experience. Therefore, we aimed to determine the depth from skin to cervical epidural space by using lateral cervical spine X-ray, which is a more intuitive method. Methods: We enrolled 102 adult patients who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
0
0
Order By: Relevance
“…Previous studies have shown higher CCC values using ultrasonography and x-ray lateral images due to their prospective study designs. 32 , 33 The study by Pak et al 13 showed similar results to our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown higher CCC values using ultrasonography and x-ray lateral images due to their prospective study designs. 32 , 33 The study by Pak et al 13 showed similar results to our study.…”
Section: Discussionsupporting
confidence: 91%
“…Various methods have been used to predict the depth from the skin to the epidural space, including demographic data and imaging modalities such as MRI, CT, Ultrasound, and x-rays. 13,[30][31][32][33][34][35] However, most studies focus on the median approach rather than the paramedian approach. Ultrasound has limitations due to LF discontinuity and difficulties in obese patients.…”
Section: Comparing With Other Studies; Significance Of Our Studymentioning
confidence: 99%